THE APPLICATION OF MATCHING GAME TO IMPROVE STUDENTS’ ENGLISH VOCABULARY MASTERY - Aswandi Aswandi (INOVISH JOURNAL, 2020)
Based on the problem found in the classroom, mastering English vocabulary is one of the weekness for the student. It seemed difficult for them to understand some words which are unfamiliar with them or even memorizing them. The use of learning media can be more effective and interesting way in learning.Therefore the researcher decided to solve these problems by applying a matching game which can be used as an alternative learning medium in learning Vocabulary. The participanst of this research were 20 Students of English Depatment. Tihis game was conducted in two cycles. Each cycle consisted of four meetings; three meetings for teaching the vocabulary by using this media, and one of them was for the test. The research findings showed that matching game could improve the students’ vocabulary mastery. It could be seen from the improvement of the students score in test. The average score of students in cycle 1 was 63 and in cycle 2 was 66. In conclusion, the implementation of matching game could improve the students’ Vocabulary mastery at first year Students of English Department at State Polytechnic of Bengkalis.